Review of The Struggle for Memory in Latin America. Recent History and Political Violence, edited by Eugenia Allier-Montaño and Emilio Crenzel - Ariel Sánchez Meertens (European Review of Latin American and Caribbean Studies, 2017)
The Struggle for Memory in Latin America. Recent History and Political Violence, edited by Eugenia Allier-Montaño and Emilio Crenzel. Palgrave Macmillan, 2015.